Property rights and economic freedom: An econometric analysis - Germinal G. Van (Economics and Econometrics Research Institute (EERI), 2020)
The purpose of this paper is to establish a positive correlation between property rights and economic freedom. It seeks to demonstrate that property rights lead to economic freedom. From a purely theoretical perspective, it has been assumed that greater access to property rights leads to economic freedom, consequently to a sustainable economic growth. To establish this correlation in the case of Africa, we applied the use of statistical tools to substantiate the validity of our economic theory. We mainly used a simple linear regression to ascertain our hypothesis.
Keywords: C33; C49; E22; O43; N27; 330; economic freedom; property rights; econometrics; macroeconomics; development economics; economic growth